Pendidikan Agama Islam Era Revolusi 4.0 pada Masa Transisi Pandemi serta Pengimplementasian Teknologi Pendidikan terhadap Digital-Blended Learning System - Salsabila, Unik Hanifah; Sari, Prima Rosita; Muhliana, Syafira Intan; Oktafiona, Tri Cahyani; Istinganah, Istinganah (Lembaga Yasin AlSys, 2021)
Talking about the world of education, of course, cannot be separated from technology. The digital era with all the conveniences that exist without knowing space, boundaries and time. Within the scope of classroom education, the teaching and learning process for both educators and students has a high level of effectiveness in conveying meaning. Education itself is also often interpreted as human maturation, because in essence this education is an effort to optimally develop the potential that exists in the human person in order to humanize humans as servants of Allah SWT. During this pandemic transition period, technology is very much needed because the teaching and learning process is carried out online, therefore applications that support learning, both applications on laptops and on gadgets. In the era of revolution 4.0, technological progress is growing. However, with the development of this technology it is either useful or not today in practical life. Progress should not be deceiving. As stated in Q.S. Ali-Imran verse 196 explains that